The Role of News Post Consumption on Facebook in Shaping Youth Perceptions of Safety and Civil Liberties during COVID-19 in the U.S., Spain, and Egypt - Reham Gamal Omar; Andreu Casero-Ripollés (Human Behavior and Emerging Technologies)
News media coverage, regardless of the platform being used, can shape people’s opinions, perceptions, behaviors, and preferences about policy, security, and civil liberties in times of crisis. This study examines the possible cultivation impact of news post exposure on Facebook on shaping threat perception. Furthermore, it aims at exploring the correlation between Facebook news exposure, preferring high security levels, and curbing some civil liberties during the COVID-19 pandemic. For this, we used the survey method (N=1309) with youths aged 18-35 in the U.S., Spain, and Egypt. Our results showed that heavy news exposure on Facebook cultivated fear and terror perceptions during the COVID-19 pandemic. Moreover, it shaped people’s preference for a tightened security environment and willingness to trade off some civil liberties. In other words, despite the different media and political systems, heavy news post consumption on Facebook can increase the tendency to give up civil liberty rights and prefer a more stringent security environment.